Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s00436-009-1358-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of indirect fluorescent antibody test and modified agglutination test for detecting Toxoplasma gondii immunoglobulin G antibodies in dog and cat

Abstract: The present study describes the comparison between a modified agglutination test (MAT) and the indirect fluorescent antibody test (IFAT) for the detection of Toxoplasma specific IgG antibodies in dog and cat sera. MAT showed an "almost perfect" agreement with IFAT in detecting positive and negative results in cat sera, where as only a "substantial" agreement was observed in dog sera due to false negative results. Differences relative to sample dilution were recorded and serological titres obtained by MAT and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…In the kit insert, the manufacturer states that: the test shows a sensitivity in excess of 99% and specificity above 99%. True prevalence (TP) was calculated using standard methods [TP=(AP+sp-1)/(se+sp-1), where AP is the apparent prevalence, se ad sp are, respectively, the sensitivity and the specificity of the test] (Bottarelli, 2012 (Andreoletti et al, 2007;Shaapan et al, 2008;Macrì et al, 2009), TP was calculated to be 38.62% (CI=34.82-42.43). Using a 1:64 cut-off point, and if an individual herd is classified as positive on the basis of having one or more seropositive animals, then 96.97% of the herds in the area would be classified as positive.…”
Section: Methodsmentioning
confidence: 99%
“…In the kit insert, the manufacturer states that: the test shows a sensitivity in excess of 99% and specificity above 99%. True prevalence (TP) was calculated using standard methods [TP=(AP+sp-1)/(se+sp-1), where AP is the apparent prevalence, se ad sp are, respectively, the sensitivity and the specificity of the test] (Bottarelli, 2012 (Andreoletti et al, 2007;Shaapan et al, 2008;Macrì et al, 2009), TP was calculated to be 38.62% (CI=34.82-42.43). Using a 1:64 cut-off point, and if an individual herd is classified as positive on the basis of having one or more seropositive animals, then 96.97% of the herds in the area would be classified as positive.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the MAT and IFAT were used, based on the results for cats obtained by Macrì et al 11 , with a concordance of 0.98 (i.e., nearly perfect), an MAT sensitivity of 97.8% and specifi city of 100%, and using IFAT as the gold standard test. visceral leishmaniasis.…”
mentioning
confidence: 99%
“…Agglutination uses tachyzoites inactivated with formalin and does not require species-specific reagents (Shaapan et al, 2008;Macrì et al, 2009). A study revealed that MAT has the highest sensitivity, followed by enzyme-linked immunosorbent assay (ELISA), whereas among serological tests, immunofluorescence antibody test (IFAT) showed the lowest sensitivity.…”
Section: Modified Agglutination Test Immunofluorescence Antibody Tesmentioning
confidence: 99%
“…The variability of the sensitivity and specificity according to the T. gondii strain employed, and subjectivity in interpreting the fluorescence reaction make it almost impossible to compare results from different laboratories. This is the reason for the numerous data in the literature that show extreme variability even in the same regions and in the same type of farm (Shaapan et al, 2008;Macrì et al, 2009). A recent study has revealed that there is an extremely low proportion of accordance between IFAT and MAT in cat and dog sera (Macrì et al, 2009).…”
Section: Modified Agglutination Test Immunofluorescence Antibody Tesmentioning
confidence: 99%